INFEKSI HANTAVIRUS PADA TIKUS DOMESTIK, PERIDOMESTIK DAN SILVATIK DI PULAU SULAWESI - Arief Mulyono; Ristiyanto Ristiyanto; Aryani Pujiyanti; Bernadus Yuliadi; Aryo Ardanto; Arum Sih Joharina; Lulus Susanti (Vektora : Jurnal Vektor dan Reservoir Penyakit, 2020)
Hantavirus infection is one of zoonotic diseases as a major global threat for human health. Anthropologic, biologic, and cultural factors contribute in the transmission of the infection in Sulawesi. In Sulawesi, some communities have a tradition of eating rat meat. A total of 52 endemic rats species is found in the area. The objective of this study were to identify the species of rats acting as hantavirus reservoir and the percentage of hantavirus seropositive in domestic, peridomestic and silvatic rats in the area. The study was conducted in four provinces, namely Central (year of 2015), North and South East (2016) and South Sulawesi (2017). Three districts of each provinces were selected. The rats captured were identified, and blood sample from each was drawn. Hantavirus infection was identified by an Elisa. The data obtained were presented descriptively. A total of 1259 rats were captured, consisted of eight genus and 27 species, ten of which were seropositive, for hantavirus infection. Six out of ten seropositive rats were record as new record of hantavirus reservoir, namely B. coelestis, B. chyssocomus, B. fratotum, B. prolatus, R. nitidus, and R. hoffmanni. The highest percentage of seropositive Hantavirus was found in peridomestic rats (5.06), while in silvic rats 4.60 and domestic rats 3.46. It is necessary to do hygiene and sanitation campaign and socialization of risks for hantavirus transmission. Abstrak Infeksi hantavirus adalah zoonosis yang telah menjadi ancaman kesehatan global dengan tikus sebagai reservoir utama zoonosis ini. Secara biologi dan antropologi penularan hantavirus rentan terjadi di Pulau Sulawesi karena di pulau ini mempunyai 52 spesies tikus endemik dan sebagian kecil masyarakat di Sulawesi mempunyai kebiasaan mengonsumsi daging tikus. Penelitian ini bertujuan untuk mengidentifikasi spesies-spesies tikus yang berperan sebagai reservoir hantavirus dan menghitung persentase seropositif hantavirus pada tikus domestik, peridomestik dan silvatik di Pulau Sulawesi. Penelitian dilakukan pada tahun 2015 di Provinsi Sulawesi Tengah, tahun 2016 di Provinsi Sulawesi Utara dan Sulawesi Tenggara, serta tahun 2017 di Sulawesi Selatan. Penangkapan tikus dilakukan di tiga kabupaten pada setiap provinsi. Tikus tertangkap diidentifikasi dan diambil spesimen darahnya. Pemeriksaan serologi dengan menggunakan teknik Elisa. Data dianalisis secara deskriptif. Hasil penelitian menunjukkan tikus tertangkap sebanyak 1.259 ekor yang terdiri dari delapan genus dan 27 spesies. Sepuluh spesies seropositif terhadap hantavirus, enam diantaranya merupakan catatan baru sebagai reservoir hantavirus. Keenam spesies tersebut adalah Bunomys coelestis, B. chyssocomus, B. fratotum, B. prolatus, R. nitidus, dan R. hoffmanni. Persentase tikus seropositif terhadap hantavirus tertinggi ditemukan pada tikus peridomestik (5,06), sedangkan pada tikus silvatik 4,60 dan tikus domestik 3,46. Perlu dilakukan kampanye peningkatan sanitasi serta sosialisasi ke masyarakat terkait risiko penularan hantavirus.